2006
DOI: 10.2105/ajph.2005.075234
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Attitudes, and Behaviors of Youths in the US Hemophilia Population: Results of a National Survey

Abstract: Young people with chronic disorders need help understanding that they can prevent complications. We identified key messages for a hemophilia prevention campaign, including exercising to ensure healthy joints and treating bleeding episodes early and adequately.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
84
1
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(89 citation statements)
references
References 9 publications
3
84
1
1
Order By: Relevance
“…In response to a questionnaire survey distributed between 2008 and 2009, 47 physicians from Europe, the US, Africa, Australia, and Central and South America reported that although they recommend bleeds be treated within 1 hour of onset, in practice only 64.6% of bleeds were treated within 1–2 hours 13. In a survey sponsored by the Centers for Disease Control and Prevention (CDC), only 31% of patients with hemophilia aged 13–21 years treated bleeding episodes within 1 hour, and 15% waited over 6 hours 14. When patients were queried, 29% replied that they did not recognize the bleeding episode, and 11% did not think the bleed was serious enough to warrant treatment.…”
Section: Barriers and Perceived Limitations To Early Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…In response to a questionnaire survey distributed between 2008 and 2009, 47 physicians from Europe, the US, Africa, Australia, and Central and South America reported that although they recommend bleeds be treated within 1 hour of onset, in practice only 64.6% of bleeds were treated within 1–2 hours 13. In a survey sponsored by the Centers for Disease Control and Prevention (CDC), only 31% of patients with hemophilia aged 13–21 years treated bleeding episodes within 1 hour, and 15% waited over 6 hours 14. When patients were queried, 29% replied that they did not recognize the bleeding episode, and 11% did not think the bleed was serious enough to warrant treatment.…”
Section: Barriers and Perceived Limitations To Early Treatmentmentioning
confidence: 99%
“…The storage and administration of clotting agents also present significant barriers to early treatment. In the aforementioned CDC-sponsored survey, 25% of patients who were not “early treaters” reported that they did not have clotting agent in their possession at the time of the bleed 14. Need for refrigeration is a further inconvenience and expense for patients, particularly those on prophylactic treatment, who must carry the clotting agents in a cooler during extended stays away from home.…”
Section: Barriers and Perceived Limitations To Early Treatmentmentioning
confidence: 99%
“…There are limited studies that assess the knowledge level of individual patients regarding the management of hemophilia [7,8,9]. An important finding of this study was that patients’ knowledge was not correlated with age, educational level, or disease severity.…”
Section: To the Editormentioning
confidence: 80%
“…It emphasized that young people with chronic disorders need help to understand how they can prevent complications. The main points for the campaigns of prevention of complications of hemophilia should include physical activity to ensure healthy joints and treating of hemorrhagic episodes early and adequately (20) . In addition to failing to obtain regular treatment, for not believing in the possibility of improvement, the adolescents surveyed also considered that they were not being adequately attended, either because they had to wait for service on weekends, when they go to service with pain or because some visits did not meet their expectation, such as physical therapy, leading them to seek these in other institutions.…”
Section: Discussionmentioning
confidence: 99%